Assessing livelihood-ecosystem interdependencies and natural resource governance in a tribally controlled region of India’s north-eastern middle Himalayas - Mark Everard; Gaurav Kataria; Smita Kumar; Nishikant Gupta (Environment, Development and Sustainability, 2021)
Mountains host high biological and cultural diversity, generating ecosystem services beneficial over multiple geographical scales but suffering significant vulnerabilities. A case study in Lileng village (Arunachal Pradesh, Indian north-east Himalayas) explored linkages between a community with protected tribal rights and the forest and river ecosystems within which they are situated. Evidence was gathered through interviews and literature review about ecosystem service benefits, using the Rapid Assessment of Wetland Ecosystem Services approach. Subsequent analysis using the social, technological, environmental, economic, political framework found close, synergistic relationships between local people and the ecosystems for which they have protected tribal rights. Authoritative local governance arrangements prioritise community subsistence needs, limiting the influence of external state government and private actors on natural resource exploitation. Further sustainable economic development could stem from recognition of the value of ecosystem services produced by intact and functional habitats, and the potential for development of ‘payment for ecosystem services’ markets in addition to ecotourism and cultural tourism. Low food sufficiency and poverty observed in a previous study conducted in Uttarakhand state of the central Indian Middle Himalayas, principal drivers of out-migration and gender/age inequalities, were not evident in Lileng or surrounding areas, apparently linked to tribal rights and authoritative local governance in Arunachal Pradesh leading to greater resource security. Better understanding of ecosystem–community relationships in areas with protected tribal rights can highlight sustainable policies and practices that may be translated into wider geo-political areas, especially in the wake of projected climate change stresses.

Ecosystem service assessment of selected wetlands of Kolkata and the Indian Gangetic Delta: multi-beneficial systems under differentiated management stress - Mark Everard; Rajiv Kangabam; Manoj Kumar Tiwari; Rob McInnes; Ritesh Kumar; Gautam Hirak Talukdar; Harry Dixon; Priya Joshi; Richard Allan; Dhaval Joshi; Lalu Das (Wetlands Ecology and Management, 2019)

Mahseer (Tor spp.) fishes of the world: status, challenges and opportunities for conservation - Adrian C. Pinder; J. Robert Britton; Andrew J. Harrison; Prakash Nautiyal; Shannon D. Bower; Steven J. Cooke; Steve Lockett; Mark Everard; Unmesh Katwate; K. Ranjeet; Sam Walton; Andy J. Danylchuk; et al. (Reviews in Fish Biology and Fisheries, 2019)

Assessing livelihood-ecosystem interdependencies and natural resource governance in Indian villages in the Middle Himalayas - Mark Everard; Nishikant Gupta; Christopher A. Scott; Prakash C. Tiwari; Bhagwati Joshi; Gaurav Kataria; Smita Kumar (Regional Environmental Change, 2019)

Rediscovering the value of urban rivers - Mark Everard; Helen L. Moggridge (Urban Ecosystems, 2012)

Towards the sustainability of the Lake Naivasha Ramsar site and its catchment - Mark Everard; David M. Harper (Hydrobiologia, 2002)

Aspects of the biodiversity of the rivers in the Lake Naivasha catchment - Mark Everard; Anthony Kuria; Michael Macharia; Jacqueline A. Vale; David M. Harper (Hydrobiologia, 2002)

Geochemical and physical characteristics of river and lake [2pt] sediments at Naivasha, Kenya - Håkan Tarras-Wahlberg; Mark Everard; David M. Harper (Hydrobiologia, 2002)

The physical attributes of the Lake Naivasha catchment rivers - Mark Everard; Jacqueline A. Vale; David M. Harper; Håkan Tarras-Wahlberg (Hydrobiologia, 2002)

THE BLUE REVOLUTION - Mark Everard (Global Ecology and Biogeography, 2001)

Towards sustainable development of still water resources - Mark Everard (Hydrobiologia, 1999)

A strategy for managing still waters in the United Kingdom - Mark Everard (Hydrobiologia, 1999)